Supervisory justice, organizational citizenship behavior, and innovative behavior: the mediating role of tacit knowledge sharing among nurses - Wah, Nur Constance; Zawawi, Dahlia; Karim, Jalina; Abu Mansor, Shazali; Anwar, Malik Ilham Sentosa; Raja Yusof, Raja Nerina (Human Resource Management Academic Research Society, 2019)
Aims: Using the perspective of social exchange theory, this study aims to provide insight on the relationship between supervisory justice, organizational citizenship behavior (OCB) and innovative behavior using mediation approach of tacit knowledge sharing. Research on the justice, OCB, and tacit knowledge sharing relationship has received minimal research attention although the role of justice and OCB is influencing the social exchange relationship quality between the employee and supervisor is well established. Method: Data were collected on a sample of 339 nurse dyads in 3 major disciplines in a Malaysian public teaching hospital. The data analyses were performed using Structural Equation Modelling (SEM) which confirmed using Partial Least Square (PLS 3.0). PLS is applied to test the research model as it has a less critical requirement of the sample size to validate. Findings: For the direct effect, the results provide support for the acceptance of all hypotheses because there are statistically significant relationships. For the indirect effect, following the mediation analysis procedure, it is concluded that tacit knowledge sharing partially mediates the relationship since both the direct and indirect effects are significant. Conclusion: This study provides a new perspective on the mediating effect of tacit knowledge sharing in predicting innovative behavior from individual factors (supervisory justice and OCB) among nurses. Contributions: From a theoretical perspective, this study contributes to the literature by introducing the mediating effect of tacit knowledge sharing on the relationships between individual factors and innovative behavior. From a practical perspective, this study provides empirical evidence on the proposed framework and provides an understanding of the relationships within a workplace allows teaching hospitals to initiate appropriate steps towards achieving their organizational goals.